Community Acceptance of Tempeh-based Artificial Meat for Food Accessibility Solutions - Siti Nursipa Wulida; Siti Irnaini Fithri; Arya Yusuf (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
Climate change is becoming a global issue that increasingly affects various sectors worldwide, including infrastructure development in Indonesia. The livestock sector contributes to significant greenhouse gas emissions and impacts global warming from large amounts of animal waste. The increasing demand for red meat has made the price of meat expensive, causing inequality in food consumption. The disparity of consumption certainly requires a new solution to this euphoria, considering that the number of emissions produced by ruminant cattle farming is many times higher than soybean or rice crops. Plant-based mock meat is the right solution as an alternative to animal meat because it can reduce the demand for red meat in the market, which will reduce livestock gas emissions that can trigger climate change. Local plant-based mock meat can realize sustainable accessibility due to its availability and ease of obtaining it. This study aims to determine the level of formula and public acceptance of mock meat made from tempeh flour as a solution to realize food accessibility in reducing red meat consumption. The method used in this research was experimental by conducting a comparative trial of public acceptability of the four products studied with the control codes F10%, F20%, and F30%. Data analysis and processing techniques were carried out with One Way Anova Ranks, Kruskal Wallis method, and Dunn's further test. The results showed that the acceptance of panelists as many as 42 people gave the highest average favorability score and the overall selection was the experiment code F30% with a mean value of 4.6 which is close to the assessment of very like compared to other development products.